Formulasi dan Aktivitas Antibakteri Patch Anti Jerawat Ekstrak Kulit Nanas (Ananas Comosus (L.) Merr.) terhadap Propionibacterium acnes dan Staphylococcus epidermidis: Formulasi dan Aktivitas Antibakteri Patch Anti Jerawat Ekstrak Kulit Nanas (Ananas Comosus (L.) Merr.) terhadap Propionibacterium acnes dan Staphylococcus epidermidis - fatimah; Gabena Indrayani Dalimunte; Minda Sari Lubis; Zulmai Rani (JURNAL FARMASI DAN MAKANAN, 2025)
Acne is a common skin issue among teenagers, primarily caused by bacterial infections from Propionibacterium acnes and Staphylococcus epidermidis. Pineapple peel has been found to contain antibacterial properties that can help treat acne. This study aims to evaluate the antibacterial effectiveness of an anti-acne patch made from pineapple peel extract (Ananas comosus (L.) Merr.) against these two bacteria. The pineapple peel extract was obtained through a reflux extraction method, followed by phytochemical screening, which identified the presence of flavonoids, saponins, tannins, and triterpenoids. The extract was then formulated into patches with concentrations of 5%, 10%, and 15% and tested for antibacterial activity. Physical evaluations showed that the patches had an appropriate pH (4.5-5.5), uniform weight (CV < 5%), acceptable thickness (0.1-0.3 mm), moisture content below 10%, and did not cause irritation in volunteers. Antibacterial testing using the agar diffusion method showed the highest inhibition zones for P. acnes at 21.1 mm and S. epidermidis at 18.2 mm at a 15% concentration. Meanwhile, the well-diffusion method showed inhibition zones ranging from 12 to 21.8 mm for P. acnes and 12.7 to 24.7 mm for S. epidermidis across various concentrations. These results suggest that pineapple peel extract and its patch formulation have strong antibacterial activity, indicating potential as an acne treatment. Keywords: anti-acne patch, pineapple peel extract, Propionibacterium acnes, Staphylococcus epidermidis, antibacterial activity.